ANALISIS PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSI, DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Rumah Sakit Pelni Jakarta) - Sarwani .; Susy Rossyana; Suhaya . (Inovasi, 2014)
This analysis reseach is about “The Effect intelectual quation, emosional quation and spiritual quation on work performance (Empirical studies to employees of Pelni Hospital Jakarta)”. The study attempted to examine a phenomena and to gain empirical evident, as well as to get a brief data on the influence of intelectual quation, emosional quation and spiritual quation on work performance. The study applied descriptive and inductive of multivariate regresion method it’s include 91 respondents as the samples. The samples were selected through proporsionate stratified sampling. The statistical tool were used is SPSS 17 software as the means to examine the data. The findings could be concluded as follows: (1) There was positive effect from all independent variables toward work performance within value influence 33,6%. (2) The results of this research indicated that spiritual quation was the greatest affecting to the employee performance was as much as 26,2%. (3) Meanwhile there are positive influence of intelectual quation was equal to 25,8%. (4) Then there are positive affecting of emosional quation was equal to 23,4%. The result suggested, to reach employees better work behavior should be encouraged constantly in order to be stable and to gain a constant synergy from all sides involved in management level of ogranization, whether it is from internal or external.                    Keywords: Intelectual Quation, Emosional Quation, Spiritual Quation and Work Performance